Probiotic in diets for Nile tilapia (Oreochromis niloticus) fingerlings (Research, Society and Development, 2022)
The objective was to evaluate the effects of the probiotics Bacillus subtilis and Bacillus cereus (4x1011 CFU kg−1) (BSC) in diets for Nile tilapia fingerlings. A total of 450 fish (average weight of 2.81 ± 0.06 g) were distributed in a completely randomized design, in 15 aquariums of 210 liters, consisting of five treatments and three replications. The isoproteic and isoenergetic experimental rations were formulated as follows: BSC1: 0% (control); BSC2: 0.6%; BSC3: 0.8%; BSC4: 1.0%; BSC5: 2.0% of probiotics per kg of feed at a concentration of 4x1011 CFU kg−1. The animals were fed the experimental diets for 30 days. At the end of the study, the productive performance was determined, and bromatological and histological analyzes of the fish were carried out. It was concluded that the probiotic did not influence the zootechnical performance of Nile tilapia fingerlings. The use of 0.8% of BSC appeared as a dietary supplementation strategy for Nile tilapia fingerlings, due to the efficacies found in the main results of body centesimal composition and in adaptations in the histomorphometry of the intestinal villi.